Berpikir Kritis dan Komputasi: Analisis Kebutuhan Media Pembelajaran di Sekolah Dasar - Windi Fitriani*; Suwarjo Suwarjo; Muhammad Nur Wangid (Universitas Syiah Kuala, 2021)
Critical thinking and computational thinking are important abilities to have in this century. The reality showed that learning of critical thinking and computational thinking have not been optimally accommodated. This study aims to analyze the learning needs in improving the critical thinking and computational thinking skills of elementary school students. The research subjects consisted of 144 grade IV students and 38 grade IV elementary school teachers spread across 12 districts in Kebumen Regency. Data collection was carried out using a questionnaire on student and teacher needs as well as semi-structured interviews with grade IV teachers. The data analysis technique was carried out in a descriptive qualitative manner. The results of data analysis showed that 65.7% of teachers wanted interactive multimedia and 77.1% agreed that meaningful learning could be created using the inquiry method. Based on these needs, the media to be developed is a combination of interactive multimedia and inquiry method namely inquiry based interactive multimedia.